The Jewish Community of Bila Tserkva: History and Modernity (Local Studies) - Хачатуров, Артемій Сергійович; Кочеткова, Ірина Валентинівна (Київський національний університет імені Тараса Шевченка, 2021)
Purpose of the study. The purpose of the work is a comprehensive study of the local history of the main trends in the historical development and the current state of the Jewish community in the city of Bila Tserkva. Research methodology. It is based on a combination of historical and geographical approaches using the methods of local history analysis and synthesis of secondary information. Research results. The Jewish people, who lived on the territory of modern Ukraine, for a long time were subjected to oppression and persecution. Since the era of Bohdan Khmelnitsky and until the fall of the Soviet Union, various restrictions and prohibitions were imposed on the ethnos under study. Despite this, the territory of the Ukrainian state became home to many Jewish generations: shtetls were created everywhere, dynasties of Hasidic tzaddiks were formed, and the like. One of the places that has undergone a significant influence of the activities of the Jewish community is the city of Bila Tserkva. This work reflects the main milestones in the formation and development of the Jewish community in the Bila Tserkva, identifies the main factors that influenced the system of settlement of the people in the city. On the basis of literary sources, including the works of O. Starodub, S. Burlaka, E. Chernetsky, the connections of the studied people with the toponymy of the city, which over the centuries took root in its system, were analyzed. In addition, the influence of the Jewish ethnos on the formation of a modern architectural ensemble was revealed, in particular the buildings of the Market Square, the choral synagogue, the city hospital, etc. This work also reveals the special role of the cemetery as an ethnocultural attribute of the town. The study also highlights current trends in the development of the Jewish community in the city: an analysis of its activities, its main social programs and relationships is carried out. Scientific novelty. During the times of the Soviet Union, full-fledged studies of the characteristics of the life of the Jewish people on the territory of Ukraine were almost not carried out, especially little attention was paid to the local history analysis of local settlements. Since independence, the number of such works has increased significantly, however, there are still significant blank spots. In this work, for the first time, a comprehensive study of the Jewish community of the Bila Tserkva is carried out. Disclosed, previously unknown aspects of local history, and the peculiarities of the life of the ethnic group in the conditions of modern Ukraine. Practical significance. The results of this work can be used for further regional studies of the Bila Tserkva region and Porosya, and as important materials for studying the characteristics of the life of the Jewish population in Ukraine. In addition, the publication can draw attention to the current state of Jewish communities, the degree of preservation of objects of the spiritual and material heritage of the people.

Мета дослідження. Мета роботи полягає у комплексному краєзнавчому дослідженні основних тенденцій історичного розвитку та сучасного стану єврейської громади м. Біла Церква. Методика дослідження. Ґрунтується на поєднанні історичного і географічного підходів з використанням методів краєзнавчого аналізу і синтезу вторинної інформації. Результати дослідження. Єврейський народ, що проживав на теренах сучасної України, тривалий час зазнавав утисків, гонінь, переслідувань. Починаючи із доби Богдана Хмельницького і аж до падіння Радянського Союзу на досліджуваний етнос накладалися різноманітні обмеження та заборони. Не зважаючи на це, територія української держави стала домівкою для багатьох єврейських поколінь: повсюдно утворювалися штетли, формувалися династії хасидських цадиків, тощо. Одне з місць, що зазнало суттєвого впливу діяльності єврейської громади є м. Біла Церква. У даній роботі висвітлено основні віхи формування та розвитку єврейської громади в Білій Церкві, встановлено основні фактори що вплинули на систему розселення народу в місті. На основі літературних джерел, зокрема праць О. Стародуб, С. Бурлаки, Є. Чернецького, було проаналізовано зв’язки досліджуваного народу із топонімікою міста, яка протягом століть укорінилася в його систему. Окрім того, було виявлено вплив єврейського етносу на формування сучасного архітектурного ансамблю, зокрема споруд Торгової площі, хоральної синагоги, міської лікарні, тощо У даній праці також розкрито особливу роль кладовища, як етнокультурного атрибуту містечка. Також у дослідженні висвітлюються сучасні тенденції розвитку єврейської громади в місті: проведено аналіз діяльності, її основних соціальних програм та взаємозв’язків. Наукова новизна. За добу Радянського Союзу повноцінні дослідження особливостей життєдіяльності єврейського народу на теренах України майже не проводились, особливо мало уваги приділялось краєзнавчому аналізу локальних поселень. Після здобуття незалежності кількість подібних робіт значно збільшилась, однак, все ще існують суттєві «білі плями». У даній роботі було вперше проведено комплексне дослідження єврейської громади Білої Церкви. Розкрито, невідомі раніше аспекти місцевої історії, та особливості життя етносу в умовах сучасної України. Практична значимість. Результати проведеної роботи можуть бути використані для подальших краєзнавчих досліджень Білоцерківського району і Поросся, та як важливі матеріали для вивчення особливостей життєдіяльності єврейського населення в Україні. Окрім цього, публікація може привернути увагу до сучасного стану єврейських громад, ступенем збереження об’єктів духовної та матеріальної спадщини народу.
Єврейська громада Білої Церкви: історія та сучасність (краєзнавче дослідження)
Keywords: Біла Церква; євреї; національні меншини; культурна спадщина; Bila Tserkva; Jews; national minorities; cultural heritage